PENGEMBANGAN BUKU PANDUAN RESEP SARAPAN UNTUK ANAK AUTIS DI SEKOLAH LUAR BIASA (SLB) - Rahmat Sanusi; Rica Ipani Tirani; Eka Lenggang Dianasari (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2021)
The problem in this study is not much breakfast menu guidebooks for autism children, The meal can affect to autism children behavior especially for emotional stability and nutritional balance. Based in this problem, the author needs to develop Breakfast Recipe Guidebooks for autism children in special education school. This research aims for the parent and teacher to assist in processing breakfast meal for autism children. And give information to parent who have autism children to know ingredient of their food that recommended and not recommended. This research the development of research and development (R&D) model. The development model did in nine stages. Based on the result of validation eligibility assessment by nutritionists, criteria of “Good” have average 3,2, material expert with criteria of “ Good” have average 3,6, the validation of the design experts with criteria of “Good”3,5. The result of response from parent and teacher in SLB Anak Briliant Batam is a small scale and the criteria of ‘Good” have average of 2,76. The results of large-scale trial, criteria of “Good” have average 3,1.